1994
DOI: 10.1111/j.1365-2621.1994.tb05540.x
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring Veal Steaks with Salt/Phosphate and Sodium Alginate/Calcium Lactate

Abstract: Quality characteristics of restructured steaks formulated with veal trimmings or veal leg meat and Na-alginate/Ca-lactate or salt (NaCl)/phosphate were evaluated. Trimmings restructured with salt/phosphate had higher (PCO.05) bind scores (measured instrumentally and by sensory) than veal trimmings restructured with Na-alginate/Ca-lactate. Salt/ phosphate (0.3-0.5%) reduced (PCO.05) purge and increased binding force and sensory score of bind in restructured veal trimmings and leg meat compared to control and Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Raharjo et al (1994) found that trimmings restructured with Na-alginate/Ca-lactate had lower binding scores than veal trimmings restructured with salt/phosphate. k-carrageenan (KC) is another polysaccharide also extracted from seaweed.…”
Section: Other Ingredientsmentioning
confidence: 99%
“…Raharjo et al (1994) found that trimmings restructured with Na-alginate/Ca-lactate had lower binding scores than veal trimmings restructured with salt/phosphate. k-carrageenan (KC) is another polysaccharide also extracted from seaweed.…”
Section: Other Ingredientsmentioning
confidence: 99%
“…Restructuring has the advantages of convenience in preparation and economy in the production due to which the restructured products are becoming important components of the processed meat industry. Restructured meat products are made by extraction of muscle proteins using salt and phosphate which forms a heat set protein gel upon subsequent cooking (Raharjo et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In production of restructured steaks from veal trimmings and leg meat, use of salt/phosphate and 0.5% sodium alginate/0.5% calcium lactate did not increase (p>0.05) juiciness, flavor, texture or color scores compared to their respective (Raharjo et al, 1994). Restructured buffalo meat rolls had markedly better sensory scores in comparison to emulsion form meat rolls and smoking had improved the appearance, flavor and acceptability of the rolls (Anjaneyulu et al, 1995).…”
Section: Sensory Qualitymentioning
confidence: 99%